Passive Recovery Promotes Superior Performance and Reduced Physiological Stress Across Different Phases of Short-Distance Repeated Sprints. Issue 9 (September 2016) - Scanlan, Aaron T.; Madueno, Maria C.
Abstract : Abstract: Scanlan, AT and Madueno, MC. Passive recovery promotes superior performance and reduced physiological stress across different phases of short-distance repeated sprints. J Strength Cond Res 30(9): 2540–2549, 2016—Limited research has examined the influence of recovery modalities on run-based repeated-sprint (RS) performance with no data available relative to the sprint phase. This study compared run-based RS performance across various sprint phases and underlying physiological responses between active and passive recoveries. Nine students (21.8 ± 3.6 years; 171.3 ± 6.4 cm; 72.8 ± 12.2 kg) completed 2 bouts (active and passive recoveries) of 10 × 20 m sprints interspersed with 30 s recoveries in a randomized crossover fashion. Sprint times and decrements were calculated for each split (0–5, 5–15, 15–20, and 0–20 m) across each sprint. Blood lactate concentration ([BLa − ]), heart rate (HR), and rating of perceived exertion (RPE) were measured at various time-points. Passive recovery promoted improved performance times ( p ⩽ 0.005) and decrements ( p ⩽ 0.045) across all splits, and lower post-test [BLa − ] ( p ⩽ 0.005), HR (bout 3 onwards) ( p ⩽ 0.014), and RPE (bout 4 onwards) when compared with active recovery. Performance differences between recoveries were less pronounced across the 0–5 m split. Temporal analyses showed significant ( p ⩽ 0.05) increases in sprint times and decrements primarily with active recovery. The present data indicate that passive recovery promoted superior performance across run-based RS, with earlier performance deterioration and greater physiological load evident during active recovery. These findings can aid the manipulation of interbout activity across RS drills to promote physiological overload and adaptation during training. Further, coaches may develop tactical strategies to overcome the detrimental effects of active recovery and optimize sprint performance in athletes during game-play.